A new hermit crab (Anomura, Paguroidea) from the upper Albian (Cretaceous) of Annopol, Poland - Fraaije, René H. B.; van Bakel, Barry W. M.; Jagt, John W. M.; Machalski, Marcin (Zootaxa, 2015)
A new diogenid paguroid, Paguristes liwinskii sp. nov., is described from upper Albian phosphorite-bearing deposits near Annopol, along the east bank of the River Vistula (Wisła), east-central Poland. This new species constitutes an additional example of Early–Mid-Cretaceous macrofaunal shift, from marine reefal limestone to siliciclastic facies, triggered by the worldwide radiation of planktonic organisms. The species described here is the earliest known member of the genus Paguristes, previously recorded from the upper Santonian/lower Campanian to the Recent.